STMO-6 Impact of the extent of resection on the survival of patients with lower grade gliomas using awake brain mapping. (6th December 2021) - Motomura, Kazuya; Chalise, Lushun; Ohka, Fumiharu; Aoki, Kosuke; Nishikawa, Tomohide; Yamaguchi, Junya; Shimizu, Hiroyuki; Kibe, Yuji; Natsume, Atsushi; Wakabayashi, Toshihiko; Saito, Ryuta
Abstract: Purpose: The aim of this study was to assess the effect of the extent of resection (EOR) of tumors on survival in a series of patients with lower-grade gliomas (LGGs) who underwent awake brain mapping. Methods: We retrospectively analyzed 126 patients with LGGs in the dominant and non-dominant hemisphere who underwent awake brain surgery at the same institution between December 2012 and May 2020. Results: The median progression-free survival (PFS) rate of patients with LGGs in the group with an EOR >100 %, including supratotal resection (n = 47; median survival [MS], not reached), was significantly higher than that in the group with an EOR <100% (n = 79; MS, 43.1 months; 95% CI: 37.8–48.4 months; p = 0.04). In patients with diffuse astrocytomas and anaplastic astrocytomas, the group with EOR >100 %, including supratotal resection (n = 25; MS, not reached), demonstrated a significantly better PFS rate than did the group with an EOR <100% (n = 45; MS, 35.8 months; 95% CI: 19.9–51.6 months; p = 0.03). Supratotal or gross total resection was correlated with better PFS in IDH-mutant type of diffuse astrocytomas and anaplastic astrocytomas (n = 19; MS, not reached vs. n = 35; MS, 40.6 months; 95% CI: 22.3–59.0 months; p = 0.02). By contrast, supratotal or gross total resection was not associated with longer PFS rates in patients with IDH-wild type of diffuse astrocytomas and anaplastic astrocytomas. Conclusions: It is noteworthy that supratotal or gross total resection significantly correlated with better PFS in IDH-mutant type of WHO grade II and III astrocytic tumors. In light of our finding that EOR did not correlate with PFS in patients with aggressive IDH-wild type of diffuse astrocytomas and anaplastic astrocytomas, we suggest treatments that are more intensive will be needed for the control of these tumors.